Supervision Under the Microscope: Critical Conversations in a Learning Community. Issue 5 (20th October 2019) - Davys, Allyson; Howard, Fiona; Rankine, Matt; Thompson, Andrew
Abstract : Development and maintenance of professional competencies are essential for practitioners across all disciplines within the helping professions to ensure safe, accountable and ethical practice. This includes the practice of supervision which is considered as a set of competencies in its own right. For many supervisors, however, there is a struggle to find the opportunity for in-depth critical reflection and review of their supervision for the purpose of continuous professional development. This paper describes a learning community for supervision where, through a process of collaborative enquiry, four experienced supervisors, in Aotearoa New Zealand, from diverse professional and practice backgrounds critically reflected on audio-recordings of their supervision of practitioners. From this focus on direct practice, the group members created a model for critique and feedback which is centred on a 'thinking aloud' process. Key themes, which included supervisor authenticity and presence, encouraging reflection, participation and uncovering assumptions and the benefits of the thinking aloud process were identified and explored. Rarely is the practice of supervision scrutinised in a group setting for the purpose of learning and development. Placing supervision practice 'under the microscope' allows for creative opportunities and the promotion of different models of supervision development.